Anthropometric indicators as a screening measure for cardiovascular risk factors in women - Azizi F; Esmaillzadeh A; Mirmiran P; Shiva N (Payesh, 2004)
Objective(s): To compare waist circumference (WC), body mass index (BMI), waist-to-hip ratio (WHpR) and waist-to-height ratio (WHtR) to predict cardiovascular risk factors in an urban adult population of women living in Tehran. Methods: This population-based cross-sectional study was conducted on 5073 women aged 18-74 years, participants of Tehran Lipid and Glucose Study (TLGS). Demographic data was collected. Anthropometric indices were measured according to standard protocol. Cut-points of BMI, WC, WHpR and WHtR were considered as 25 kg/rrrchr('39'), 80cm, 0.8 and 0.5, respectively. Blood pressure was measured and hypertension was defined based on JNC VI. Biochemical analysis was conducted on fasting blood samples. Diabetes was defined as FBS2:126 mg/di or 2liBG>= 200 mg/di and dyslipidemia based on ATP II. The presence of "at least one risk factor" from the four major cardiovascular risk factors (hypertension, dyslipidemia, diabetes and smoking) was also evaluated. Results: The mean age of women was 39.9±14.6.  The mean BMI, WC, WHpR and WHtR were 27.1±1.5 kg/rrrchr('39'), 86.5±13.5 cm and 0.83±0.08 and 0.55±0.08, respectively. Of the four anthropometric measures, subjects with abnormal WC had the highest odds for cardiovascular disease. Waist circumference had the highest sensitivity and specificity to identify subjects with risk factors in both 18-39 years and 40-74 years age categories. No combination of indicators had higher average sensitivity+ specificity than WC. Waist circumference had the highest area under the ROC and a higher percentage of correct prediction than BMI, WHpR and WHtR. Conclusion: It is concluded that WC is the best screening measure for cardiovascular risk factors compared to BMI, WHpR and WHtR in adult women.